GERAKAN LITERASI BUDAYA DI SEKOLAH DASAR - Tsaqifah, Ainun; Siti Aisyiah; Mega Novita M. Yani; Muhammad Nawir; Muhajir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Cultural Literacy Movement at UPT SPF SD Inpres Mariso 1 and to analyze its supporting factors, obstacles, and impacts on students. This research uses a descriptive qualitative approach, with the principal, teachers, and students in grades IV and V as participants. Data were collected through observation, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña interactive model. The findings show that the Cultural Literacy Movement is implemented through reading habits using Indonesian folktales, integration of cultural values into learning, and project-based co-curricular activities. These activities improve students’ cultural understanding, social skills, and character development. Therefore, the Cultural Literacy Movement plays an important role in strengthening students’ character and cultural identity in elementary schools.